Centro de Atenção Integrada à Saúde Mental Eduardo Ribeiro (CAISM EDUARDO RIBEIRO) - Santos, Eglantina Batista dos (Brasil, 2022)
Mental disorders are highly prevalent chronic diseases worldwide and contribute to early morbidity, disability, and mortality. (ABP, 2020) According to the WHO (2022a), in the first year of the COVID-19 pandemic, the rates of anxiety and depression increased by 25% globally. Also, according to WHO (2022b), work is a key point in mental health. However, a bad work environment can lead to physical and mental health problems, alcohol abuse and drugs, absence from work and loss of productivity. In this scenario, a serious problem faced in Brazil is the lack of beds specialized psychiatrics. With the psychiatric reform many beds were closed in favor of deinstitutionalization and today Brazil has poor coverage in that mode. The closing of psychiatric beds proved to be ineffective, resulting in the overcrowding of psychiatric emergencies and an increase in street dwellers. (KAWAKAMI, PRATES, TENG apud TAMAI, 2015)